EFFECT OF PORTLAND-POZZOLAN CEMENTS ON CONCRETE MATURITY - Arın YILMAZ (Pamukkale University Journal of Engineering Sciences, 2004)
The maturity concept expressed by the combined effect of time and temperature on the concrete is a useful technique for prediction of the strength gain of concrete. According to maturity concept, samples of the same concrete at same maturity whatever combination of temperature and time, have approximately the same strength. Many maturity functions have been proposed for the last 50 years. The validity of these functions are only for ordinary portland cements. In this study, the suitable of traditional maturity functions for different types of Portland-pozzolan cements were investigated and a new maturity-strength relationship was tried to be established. For this purpose, four different pozzolans and one Portland cement was selected. Portland-pozzolan cements were prepared by using three different replacement amounts of % 5, % 20 and 40 % by weight of cement.